Pandangan Al-Qurâ€™an dalam Beragama - Komaru Zaman; Ahmat Fuat Rifangi (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Humans are created with a wide variety of ethnicities and diversity, therefore it is impossible for humans to have the same personality and character. So that to direct it, humans really need religion so that in their life there is harmony even though they come from various circles, different races and races As the Qur'an has explained clearly: â€œAnd if your god wills, surely the faith of all the people on earth throughout it So do you (want) to force people so that they become people who believe all for them.â€